(untitled) (Chattagram Maa-O-Shishu Hospital Medical College Journal, 2024)
Background: For Liver, spleen and kidney measurement, available data are not always representative for all population. This study was aimed to find out the normal measurement of kidney, liver, spleen using ultrasonography at Chattogram, Bangladesh. Materials and methods: Among a total of 3699 subjects (Male: Female 1.4:1; median age 35 years) without any liver, splenic or renal diseases ultrasonographic images of these organs were from 2780, 1596, and 2780 individuals respectively. Measurements were taken for liver length, splenic length and breadth and renal length, breadth and cortical thickness. Results: The average liver length in neonates and infants were 5.2 and 6.5 cm in females and 5.7 and 6.6 cm in males. After 20 years of age, average liver sizes ranged from 11.1 to 11.6 cm. The average spleen length in neonates and infants were 3.5 and 5.6 cm in females and 5.7 and 6.4 cm in males. After 20 years of age, it ranged from 8.2 to 9.0 cm. The average renal length in neonates and infants were 4.2 and 5.3 cm for right kidney and 4.3 and 5.5 cm for left kidney in females. In male neonates and infants were 4.9 and 5.3 cm for right kidney and 4.8 and 5.6 cm for left kidney. After 20 years of age, it ranged from 9.0 to 9.7 cm for right kidney and from 9.6 to 10.2 cm for left kidney. Conclusion: These values may be used as reference for normal liver, spleen and kidney dimensions for populations of Chattogram, Bangladesh. Chatt Maa Shi Hosp Med Coll J; Vol.22 (2); July 2023; Page 36-41